THE IMPORTANCE OF DEVELOPING CREATIVITY IN STUDENTS - Hilola Ziyabayeva; Mukhlisa Omonova (Bright Mind Publishing, 2025)
This article discusses the importance of developing creativity in students, the formation of teachers' creative abilities and their role in their work. It discusses the creative qualities of a teacher. It discusses creative thinking in the educational process, the creation of various ideas, and actions to increase the effectiveness of the lesson through discussions.
Keywords: Creativity, creative personality, creative thinking, creativity in education.